Association of vitamin D in patients with periodontitis: A cross‐sectional study. (16th March 2020) - Isola, Gaetano; Alibrandi, Angela; Rapisarda, Ernesto; Matarese, Giovanni; Williams, Ray C.; Leonardi, Rosalia
Abstract: Background and Objective: Vitamin D has been considered to possess anti‐inflammatory and antimicrobial activity, which may be a link for the known interaction of periodontitis (CP) and coronary heart disease (CHD). This study investigated the association between serum vitamin D levels and periodontitis in patients with CP and with CHD. Furthermore, the objective was to determine whether periodontitis and CHD had an impact on serum vitamin D levels. Material and Methods: Using a cross‐sectional design, a total of 46 patients with CP, 45 patients with CHD, 45 patients with both CP and CHD, and 43 healthy patients were enrolled in the present study. Results: Patients in the CP (17.4 ± 5.2 ng/mL) and in the CP + CHD (16.5 ± 5.6 ng/mL) group presented a significantly lower mean serum level of 25(OH)vitamin D compared to patients in the CHD (24.6 ± 3.7 ng/mL) and healthy control groups (29.9 ± 5.4 ng/mL) ( P  < .001). 25(OH)vitamin D levels were positively correlated with the number of teeth and negatively with C‐reactive protein (CRP) and all periodontal parameters ( P  < .001). In all patients, there was a proportional increase of 25(OH)vitamin D levels with a progressive increase in number of teeth ( P ‐trend <.001) while there were a proportional decrease in 25(OH)vitamin D levels with a progressive increase in clinical attachment level (CAL, P ‐trend = .001), probing depth (PD, P ‐trend = .006), and bleeding sites (BOP, P ‐trend <.001) levels. Conclusion: Patients with CP and CP + CHD presented significantly lower serum levels of vitamin D compared to CHD and healthy controls. Moreover, the presence of CP negatively influenced serum vitamin D levels.